2018
DOI: 10.4236/ojce.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Compressive and Flexural Strength of Recycled Reactive Powder Concrete Containing Finely Dispersed Local Wastes

Abstract: The main objective of this experimental study is to investigate the behavior of Recycled Reactive Powder Concrete (RRPC) developed from finely dispersed local waste raw materials. In this study, RRPC was developed by utilizing local wastes (finely dispersed waste glass powder, waste fly ash and waste ceramic powder) together with Portland cement, fine sand, admixture, steel fibers and water through full replacement of silica fume as well as quartz powder for sustainable construction practice. In this study, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Waste glass powder in combination with RHA by replacing SF completely in the RPC mix showed improved strength with 20% RHA and 80% fine glass powder combination (Asteray et al 2017) whereas the utilization of glass powder at 20% instead of quartz powder partially enhanced the mechanical performance of RPC, however could not completely replace quartz powder for the production of high strength RPC (Kushartomo et al 2015).…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste glass powder in combination with RHA by replacing SF completely in the RPC mix showed improved strength with 20% RHA and 80% fine glass powder combination (Asteray et al 2017) whereas the utilization of glass powder at 20% instead of quartz powder partially enhanced the mechanical performance of RPC, however could not completely replace quartz powder for the production of high strength RPC (Kushartomo et al 2015).…”
Section: R a F Tmentioning
confidence: 99%
“…Waste management in construction sector reduce the intake of natural resources for construction by utilizing waste materials as substitutes thereby averting the global problem D r a f t (Asteray et al 2018). The construction industry is moving towards the pace of sustainable construction by reducing the life cycle cost of the building materials through utilization of waste materials and industrial by-products (Vijayalakshmi.…”
Section: R a F T 1 Introductionmentioning
confidence: 99%
“…Furthermore, multiple research projects have been conducted to explore the impact and synergistic effects of various SCMs, in addition to SF, in the construction of environmentally friendly RPC concrete [38,40,41]. Based on the foregoing findings, it is reasonable to conclude that GP offers the potential as a viable option for traditional materials in the development of RPC [42,43].…”
Section: Introductionmentioning
confidence: 95%
“…Rice Husk Ash (RHA) has been used as a partial substitute for SF [2], [8], [9] and its effect on the mechanical and durability properties of RPC was determined. Test results from the findings of [2] showed that RPC containing RHA has satisfactory mechanical and durability performance under both normal and steam curing condition.…”
Section: Introductionmentioning
confidence: 99%